Analisis Isi Kuantitatif Berita LINE TODAY Selama Periode Satu Bulan (Periode 1-31 Desember 2020) - Maharani, Puan Ega; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2020)
LINE TODAY is one of LINE's newsfeed features. News recommended by LINE TODAY is entered every day through broadcast messages sent directly to its users. The purpose of this study was to see what types of news and online news portals were widely recommended and to calculate the frequency and percentage of news categories. The selection for the period 1-31 December 2020 was due to the end of the year conditions, where the author wanted to see flashback news or kaleidoscope activities carried out by LINE TODAY. Quantitative descriptive content analysis method is used to analyze LINE TODAY news. Based on the analysis conducted, data obtained were 851 news. Type of News is the most recommended with a total of 329 news with a percentage of 39% and news from Kumparan which is widely recommended by LINE TODAY with a total of 110 news during a period of one month.   Keywords: Content Analysis, LINE TODAY, Kaleidoscope